Usulan Perbaikan Kualitas Stiker Cromo dengan Metode FMEA dan FTA pada CV.Usaha Mandiri Makmur - Biri, Fernandez Puli Lango; Alek , Alek (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Nowadays, there are more and more developments being shown by companies operating in the printing sector, which has resulted in more competition. Companies must show their best performance so they can attract more customers. The products produced include cromo sticker paper and vinyl sticker paper. In this research, the product that is the object of research is Cromo sticker paper, because the percentage of defects is higher. This research aims to determine the number of defects, the causes of defects, and provide suggestions for improving the quality of cromo sticker paper. The methods used are the FMEA and FTA methods. The results of this research found 3 types of defects, namely inappropriate color, cutting machine, and torn paper. The analysis carried out found that the causes of defects came from negligence, haste, operators' lack of understanding, lack of machine maintenance, paper storage without SOPs, and dusty processes. Quality improvement is carried out using the 5W+1H method and creating an SOP that provides recommendations for quality improvement in the form of carrying out supervision, making activity schedules according to the SOP, options for increasing working hours by holding overtime according to the SOP, storing paper stock in the warehouse according to the SOP, periodically cleaning the factory environment and process of sending goods according to SOP.